Pomen prehrane pri nekaterih dermatoloških boleznih - Dolenc-Voljč, Mateja (Medicinski razgledi, 2001)
Discussions on importance of nutrition in the treatment of some skin diseases are continuing for many years. Opinions are frequently controversial and are formed mainly on the basis of various empirical experiences. The role of diet alone is difficult to evaluate because of various concomittant treatment schedules. In the last several years only scarce new data were published, controlled study data on the importance of nutrition have been rarely reported. The importance of diet for successful treatment is established for some groups of patients with urticaria and atopic dermatitis, Dermatitis herpetiformis Duhring and in vitamin deficiencies. In the last years more attention has been dedicated to psoriasis again. Results of newer studies confirm the beneficial effect of omega-3 fatty acids in psoriasis. In other skin diseases the role of diet is doubtful and can be recommended as secondary, non-specific measure only. The purpose of this article is to present the current data about the role of diet in some groups of patients with skin diseases. The role of nutritive allergy in allergic skin diseases isdiscussed.
Keywords: Dermatitis herpetiformis; Nutrition; Dermatitis atopični; Food hypersensitivity; Hrana, alergija; Urticaria; food; Prehrana; Dermatitis, atopic; Psoriasis; Psoriaza; Acne rosacea; Urtikarija; Akna rozacea; Avitaminosis; Avitaminoza; Dermatitis herpetiformni; dermatologija; kožne bolezni